Implementasi Model Pembelajaran CTL Terhadap Kemampuan Berpikir Reflektif Peserta Didik Pada Matapelajaran Fikih - Salamudin, Ceceng; Alidia, Pipi (STAI Al-Musaddadiyah Garut, 2025)
Islamic Religious Education is expected to be able to produce humans who always strive to perfect faith, piety and noble character which includes ethics, character or morals as a manifestation of education. A poor learning process is one of the problems in the world of education. Reflective thinking is one of the thoughts needed in the problem-solving process. The process of learning, researching, and solving problems will maximize the results if one's reflective thinking skills are good enough. The CTL model encourages learners to make connections between the knowledge they have and the application in their daily lives, so that CTL learning can get learners involved in meaningful activities and solidify the knowledge that learners have. This research focuses more on the implementation of the CTL model on the reflective ability of students in fiqh subjects. This research method uses descriptive analytical qualitative research, which is research that provides a description of factual and systematic situations and conditions regarding factors, properties, and relationships between phenomena owned to find out the basics. The results showed the implementation of the Contextual Teaching and Learning (CTL) learning model for fiqhsubjects at MA Hidayatul Faizien Bayongbong Garut through the process of constructing in fiqh learning, encouraging students to find their own meaning (inquiry), encouraging students to know something by asking (questioning), creating a learning community, students modeling in fiqh learning, reflecting in fiqh learning, using authentic assessment in fiqh learning. Keywords: CTL Learning Model, Fikh Subject, Reflective Thinking